Persistence in the treatment of overactive bladder syndrome (OAB) with mirabegron in a multicenter clinical study. (March 2017) - Martan, Alois; Masata, Jaromir; Krhut, Jan; Zachoval, Roman; Hanus, Tomas; Svabik, Kamil
Abstract: Objective: The objective of this project was to evaluate treatment persistence in patients being treated for overactive bladder syndrome (OAB) with mirabegron, employing clinical follow-up in a prospective, multicenter study. Study design: This is an analysis of patients who started treatment with mirabegron between May and September 2014 and were evaluated 1 year after treatment commenced. During this evaluation we determined how many patients stopped treatment and established their reasons for discontinuation. Results: 206 patients being treated for OAB with mirabegron were evaluated a year after starting treatment. It emerged that 60 patients (29.1%) had discontinued the treatment, citing the following reasons: 24/60 insufficient treatment efficacy, 26/60 other reasons, while 10 members of the group discontinued treatment because of side effects. 75 out of 206 patients were ≤60 years old and 28% terminated the study prematurely: 131 out of 206 were >60 years old and 29.2% terminated the study prematurely. In the group of patients without previous OAB treatment 35.7% discontinued treatment with mirabegron, while 28.1% of patients with previous anticholinergic treatment discontinued treatment. Conclusion: In our clinical prospective multicenter study, persistence in treatment with mirabegron reached a figure of 71%.